2009
DOI: 10.1103/physreve.80.036602
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic diffraction radiation of a subwavelength-hole array excited by an electron beam

Abstract: This paper explores the physics of the electromagnetic diffraction radiation of a subwavelength holes array excited by a set of evanescent waves generated by a line charge of electron beam moving parallel to the array. Activated by a uniformly moving line charge, numerous physical phenomena occur such as the diffraction radiation on both sides of the array as well as the electromagnetic penetration or transmission below or above the cut-off through the holes. As a result the subwavelength holes array becomes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Recently, intense investigation has demonstrated that the combination of electronics, photonics, and nanotechnology is a promising method to generate radiation, ranging from terahertz to visible light [1][2][3][4][5][6][7]. Among these studies, Refs.…”
mentioning
confidence: 99%
“…Recently, intense investigation has demonstrated that the combination of electronics, photonics, and nanotechnology is a promising method to generate radiation, ranging from terahertz to visible light [1][2][3][4][5][6][7]. Among these studies, Refs.…”
mentioning
confidence: 99%
“…T has been shown that under the excitation of a line current of electron beam, the sub-wavelength holes array (SHA) becomes a diffraction radiation array, and the SHA diffraction radiation is a special mechanism with unique distinguished characteristics [1,2]. In this paper we reveal that the dielectric medium loading in the lower half-space of the array (SHAM) brings surprising changes to the behaviors of the diffraction radiation, furthermore many interesting and important phenomena occur.…”
Section: Introductionmentioning
confidence: 96%
“…Figure 1 shows the contour map of the diffraction radiation, which demonstrate that it is unique radiation behavior. In the upper half-space, the electrons excited the diffraction radiation as the structure without loading medium in reference [2]. However, in the lower half-space, the loading dielectric medium brings essential changes to the behaviors of the radiation.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important research areas in THz regime is the radiation sources, and in order to fill the THz gap the studies on this area are extremely intensive [1][2][3]. It seems linear electron-beam driven sources provide good ways to develop (approaches to) the compact and room temperature THz sources and there are a lot of published papers concerned the topics of backward-wave oscillators (BWO), extended interaction oscillators (EIO), orotron and free-electron lasers (FELs) and so on [4][5][6][7][8][9][10][11][12][13][14][15]. However, among these Electron-beam driven oscillator-sources, there is a key problem limited the development in THz regime: the starting current density.…”
Section: Introductionmentioning
confidence: 99%